Investigation of the molecular mechanisms of functional innovation - Caffrey, Brian E. (Trinity College (Dublin, Ireland). School of Genetics and Microbiology, 2012)
The robustness to perturbations and evolvability of genomes are two major principles that govern the emergence of genetic diversity across all forms of life. Functional innovations that occur through the genetic diversity cryptically present themselves in the populations. The mechanisms underlying the emergence of biological innovations from this genetic diversity have been a major question in evolutionary biology.
Keywords: Genetics & Microbiology, Ph.D.; Ph.D. Trinity College Dublin.